2016
DOI: 10.3174/ajnr.a4730
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Suboccipital Musculature on Symptom Severity and Recovery after Mild Traumatic Brain Injury

Abstract: BACKGROUND AND PURPOSE:Neck musculature mass has been suggested as a biomechanical contributor to injury severity in mild traumatic brain injury. We sought to determine how the cross-sectional areas of the suboccipital muscles affect symptom severity, neurocognitive performance, and recovery time in patients with mild traumatic brain injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…Reduced CSA has been associated with greater symptom severity, longer recovery time, and headaches. 2 Loss of muscle mass can also occur when the density of a muscle decreases as a result of increased fatty infiltration. 1 In this case, the CSA of the muscle is seen to increase, whereas its density and functional capacity decrease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced CSA has been associated with greater symptom severity, longer recovery time, and headaches. 2 Loss of muscle mass can also occur when the density of a muscle decreases as a result of increased fatty infiltration. 1 In this case, the CSA of the muscle is seen to increase, whereas its density and functional capacity decrease.…”
Section: Discussionmentioning
confidence: 99%
“…Far more common are acute and chronic symptoms of head and neck pain, which are associated with soft tissue pathologies subsequent to whiplash-type distortions of the upper cervical spine. 1,2 Unfortunately, the source of these chronic symptoms is not clearly understood.…”
Section: Introductionmentioning
confidence: 99%
“…The architecture of muscle, particularly the cross-sectional area (CSA), is a predictor of its force generation [15]. Previous research has focused on the CSA or relative CSA of the RCPmi muscle as biomechanical contributors to cervicocephalic pain syndrome, mild traumatic brain injury (mTBI), and headache syndromes [10][11][12][13]16]. Several studies have shown that the CSA of adult RCPmi muscles is negatively correlated with the severity of chronic headaches [10][11][12][13]16].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has focused on the CSA or relative CSA of the RCPmi muscle as biomechanical contributors to cervicocephalic pain syndrome, mild traumatic brain injury (mTBI), and headache syndromes [10][11][12][13]16]. Several studies have shown that the CSA of adult RCPmi muscles is negatively correlated with the severity of chronic headaches [10][11][12][13]16]. Fernfindez-de-las-Penas et al [10,11] have shown that reduced axial CSA of the RCPmi is correlated with symptom severity in patients with chronic tension-type headache (CTTH) and mTBI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation